Integrated Microfluidic Chip for Cell Culture and Stimulation and Magnetic Bead-Based Biomarker Detection - Ruffert, Christine; Ramadan, Qasem; Ruegg, Matthieu; Vergeres, Guy; A. M. Gijs, Martin (Micro and Nanosystems, 2014)
A microfluidic chip has been designed and fabricated for culture and stimulation of cells, and for subsequent cell biomarker monitoring using an on-chip performed magnetic bead-based immunoassay. As a proof of concept, we demonstrate monocytic cell (U937) culture, subsequent stimulation of the cells with lipopolysaccharide (LPS), and fluorescent detection of the cytokine interleukin-6 (IL6) released by the cells using magnetic beads functionalized with fluorescent antibodies (Abs) against IL6. The chip comprises two compartments which are separated by a vertical pillar-based filter. The immune cells are cultured in the first compartment and then differentiated to macrophages, while the second compartment is used for the immunoassay that is performed on magnetic beads, the surface of which is conjugated to an IL6-specific antibody. The magnetic beads are kept in place in the detection zone by soft magnetic tips that are part of an electromagnet circuit. The filter with a pore size of 2 μm allows the released cytokines to diffuse from the cell culture / cell stimulation chamber downstream to the chamber containing the magnetic beads, but prevents an exchange of cells and magnetic beads. We found a significant increase of the fluorescence obtained from streptavidin-phycoerythrin (PE)-IL6 conjugates formed on the surface of the magnetic beads, after treating the macrophages with LPS.
Keywords: Cytokines